Thio-click reaction of 2-deoxy-exo-glycals towards new glycomimetics: stereoselective synthesis of C-2-deoxy-d-glycopyranosyl compounds. (25th March 2019) - József, János; Juhász, László; Somsák, László
Abstract : Photoinitiated addition of thiols to 2-deoxy- exo -glycals obtained from endo -glycals ofd - arabino, d - lyxo, d - erythro andd - threo configurations resulted in highly regio- and stereoselective formation of glycosylmethyl sulfide type glycomimetics. Abstract : A series of 2-deoxy-glycopyranosyl cyanides withd - arabino, d - lyxo, d - erythro, andd - threo configurations was synthesized from the corresponding glycals via 2-deoxy-glycopyranosyl acetates. The cyanides were transformed to anhydro-aldose tosylhydrazones by reduction with NaH2 PO2 /Ra-Ni in the presence of tosylhydrazine. The tosylhydrazones furnished 2-deoxy- exo -glycals under modified Bamford–Stevens conditions. Photoinitiated thiol–ene additions of these exo -glycals resulted in the corresponding C -(2-deoxy-d -glycopyranosyl)methyl sulfides in medium to good yields with exclusive regio- and stereoselectivities in most cases. Several disaccharide mimics with a C–S moiety in place of the glycosidic oxygen were also obtained.